Long-term durability after surgical aortic valve replacement with the Trifecta and the Intuity valve—a comparative analysis. (5th November 2021) - Werner, Paul; Coti, Iuliana; Kaider, Alexandra; Gritsch, Jasmin; Mach, Markus; Kocher, Alfred; Laufer, Guenther; Andreas, Martin
Abstract:  : OBJECTIVES: Long-term durability of surgical bio-prostheses is a key factor, especially in the era of transcatheter aortic valve replacement. We compared the incidence of structural valve deterioration (SVD) between patients undergoing surgical aortic valve replacement (SAVR) with the Trifecta (Abbott Laboratories, Abbott Park, IL, USA) or the Intuity valve (Edwards Lifesciences, Irvine, CA, USA). METHODS: Between April 2010 and May 2020, 1118 patients underwent SAVR with the Trifecta ( n  = 346) and the Intuity ( n  = 772) valve at a single centre. A total of 1070 patients (Trifecta n  = 298, Intuity n  = 772) were analysed after the exclusion of patients with pure regurgitation and endocarditis. Retro- and prospective echocardiographic and clinical follow-up was performed. Cox proportional hazards regression models were performed to identify prognostic factors for SVD, aortic re-interventions and mortality. RESULTS: With 27 cases (Trifecta n = 23, Intuity n = 4) of SVD observed, cumulative incidence of SVD was significantly higher in the Trifecta cohort (P < 0.001). Implantation of a Trifecta valve [hazard ratio (HR) 11.20; 95% confidence interval 3.79–33.09], log-transformed preoperative creatinine (HR 2.47; 1.37–4.44) and sex (male HR 0.42; 0.19–0.92) emerged as prognostic factors of SVD. A significantly higher cumulative incidence of re-interventions was observed in the Trifecta cohort ( P  = 0.004) and valve type was an independent time-varying risk factor (HR at 12 months 2.78; 95% confidence interval 1.42–5.45). Overall, no significant differences in all-cause mortality were observed between the groups (log-rank test: P  = 0.052). CONCLUSIONS: SVD was significantly more frequent in patients receiving a Trifecta valve and its implantation was an independent risk factor for the occurrence of SVD and aortic valve re-interventions. This comparative analysis of 2 low-gradient bioprosthesis put the long-term durability of the Trifecta valve in question and need to be taken into consideration when performing bioprosthetic SAVR. Abstract : Within the last decades, an evident trend toward an increased use of bioprosthetic valves in patients undergoing surgical aortic valve replacement (SAVR) has been observed [1].